"N-alkyl diketopyrrolopyrrole-based fluorophores for luminescent solar concentrators: Effect of the alkyl chain on dye efficiency". (December 2016) - Lucarelli, Jonathan; Lessi, Marco; Manzini, Chiara; Minei, Pierpaolo; Bellina, Fabio; Pucci, Andrea
Abstract: We report on the preparation of luminescent solar concentrators (LSCs) made of poly(methyl methacrylate) (PMMA) thin films doped with six new diketopyrrolopyrrole (DPP) fluorophores obtained in good yields by using simple N -alkylation and direct CH arylation synthetic strategies. Spectroscopic investigations in solution and in PMMA thin films combined with photocurrent measurements revealed that the branched alkyl chains were efficient in preventing DPP segregation from the PMMA matrix thanks to their higher steric hindrance. The aromatic substituent was found to expand DPP conjugation but favoured DPP adverse aggregation, thus affecting fluorescence emission and photocurrents of PMMA films. The worthwhile combination of the appropriate alkyl chain and aromatic moieties assured to achieve optical efficiency of 6.8% that was comparable to that of PMMA LSCs of the state-of-the art (7.2%). Graphical abstract: Highlights: DPPs exhibit high fluorescence quantum yields and exceptional thermal and photostability. Alkyl chains strongly affect DPP aggregation behaviour in solid state. Branched 2-ethylhexyl chains allowed highest DPP dispersion in PMMA. 2-ethylhexyl DPP/PMMA films exhibit highest fluorescence and photocurrent intensities. 2-ethylhexyl DPP/PMMA LSCs yield maximum optical efficiencies of 6.8%.